Evaluation of the 2012 18th Maternal and Child Health (MCH) Epidemiology and 22nd City Mat CH MCH Urban Leadership Conference: Six Month Impact on Science, Program, and Policy. - Arellano, Danielle; Goodman, David; Howlette, Travis; Kroelinger, Charlan; Law, Mark; Phillips, Donna; Jones, Jessica; Brantley, Mary; Fitzgerald, Maureen (Maternal & Child Health Journal, 2014)
The 18th Maternal and Child Health (MCH) Epidemiology and 22nd CityMatCH MCH Urban Leadership Conference took place in December 2012, covering MCH science, program, and policy issues. Assessing the impact of the Conference on attendees' work 6 months post-Conference provides information critical to understanding the impact and the use of new partnerships, knowledge, and skills gained during the Conference. Evaluation assessments, which included collection of quantitative and qualitative data, were administered at two time points: at Conference registration and 6 months post-Conference. The evaluation files were merged using computer IP address, linking responses from each assessment. Percentages of attendees reporting Conference impacts were calculated from quantitative data, and common themes and supporting examples were identified from qualitative data. Online registration was completed by 650 individuals. Of registrants, 30 % responded to the 6 month post-Conference assessment. Between registration and 6 month post-Conference evaluation, the distribution of respondents did not significantly differ by organizational affiliation. In the 6 months following the Conference, 65 % of respondents reported pursuing a networking interaction; 96 % shared knowledge from the Conference with co-workers and others in their agency; and 74 % utilized knowledge from the Conference to translate data into public health action. The Conference produced far-reaching impacts among Conference attendees. The Conference served as a platform for networking, knowledge sharing, and attaining skills that advance the work of attendees, with the potential of impacting organizational and workforce capacity. Increasing capacity could improve MCH programs, policies, and services, ultimately impacting the health of women, infants, and children.